Cloud Computing in Library - Pečeliūnaitė, Angelė (Bibliotheca Lituana, 2014)
The article analyses the possibility of how Cloud Computing can be used by libraries to organise activities online. In order to achieve a uniform understanding of the essence of technology SaaS, IaaS, and PaaS, the article discusses the Cloud Computing services, which can be used for the relocation of libraries to the Internet. The improvement of the general activity of libraries in the digital age, the analysis of the international experience in the libraries are examples. Also the article discusses the results of a survey of the Lithuanian scientific community that confirms that 90% of the scientific community is in the interest of getting full access to e-publications online. It is concluded that the decrease in funding for libraries, Cloud Computing can be an economically beneficial step, expanding the library services and improving their quality.
Keywords: cloud computing; SaaS; IaaS; PaaS; LaaS service; digital information management; virtual library; an electronic reading room; electronic publications; scientific community